2014
DOI: 10.3136/fstr.20.121
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fatty Acid Distribution in Different Acyl Lipids of Colored Rice Bran Cultivars

Abstract: Keywords: colored rice, diacylglycerols, fatty acid distributions, free fatty acids, phospholipids, triacylglycerols IntroductionRice (Oryza sativa L.) is one of the staple cereal crops cultivated in the world and feeds more than half of the world's population (Xue et al., 2008). Colored rices, which are found in Japan, are also classified as Oryza sativa L. Rice is primarily processed and consumed as a whole grain. Moreover, rice grain quality is an important economic trait that influences rice production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…This resutl was very interesting because linoleic acid is the main Omega-6-FA, having multiple cardiovascular or mental disease prevention functions. Our results differed from some other studies where they found that oleic acid accounted for the highest amount among FAs (Yoshida et al, 2011(Yoshida et al, , 2014. We also obtained high content of monounsaturated fatty acids, especially oleic acid, which is preferable as cooking oil because it could improve the stability and nutrition value of rice (Galanakis, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This resutl was very interesting because linoleic acid is the main Omega-6-FA, having multiple cardiovascular or mental disease prevention functions. Our results differed from some other studies where they found that oleic acid accounted for the highest amount among FAs (Yoshida et al, 2011(Yoshida et al, , 2014. We also obtained high content of monounsaturated fatty acids, especially oleic acid, which is preferable as cooking oil because it could improve the stability and nutrition value of rice (Galanakis, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Among five main FAs, 97% of total FAs was the palmitic, linoleic and oleic. The same results were obtained in other studies (Hwang et al, 2002;Cho et al, 2006;Yoshida et al, 2011Yoshida et al, , 2014Yang et al, 2018). Other study also indicated that FA composition of rice grains was noticeably high compared to oats, maize, wheat, barley and other cereals (Thomas et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Rice grain lipids are mainly free fatty acids or fatty acid glycerol esters (glycerides) and are a minor component of rice grain (Table ). Palmitic acid (C 16:0) accounts for 17.9–28.7% of total fatty acids in milled rice, oleic (C 18:1) at 29.6–46.1% and linoleic acids (C 18:2) at 21.3–46.1% are the major fatty acid component of rice lipids . Rice bran is the most lipid enriched component of the milling fractions (Table ) containing mostly neutral lipids such as triacylglycerols, while milled rice contains more polar lipids, including phospholipids and glycolipids, than other milling fractions…”
Section: Rice Lipids Impact On Rice Starch Digestionmentioning
confidence: 99%